Titanium carbide micron tube as well as preparation method and application thereof
By using SiC fibers and Ti powder in anhydrous ethanol solvent for heating and stirring and molten salt reaction, combined with vacuum high-temperature heat treatment, high-purity and accurate morphology were successfully prepared, which solved the problems of high preparation costs and complex processes in the prior art, and improved the chemical stability and electrical conductivity of the material.
Patent Information
- Application Number
- CN202411882197.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art has problems such as high production cost, complex process, and difficult to control purity and morphology when preparing titanium carbide microtubes.
SiC fibers were used in anhydrous ethanol solvent, mixed with Ti powder, heated and stirred, and molten salt reaction was carried out. Through the interfacial decomposition and diffusion mechanism, SiC fibers containing Ti3SiC2 coating were formed, and high-temperature heat treatment was carried out under vacuum to decompose and form TiC microtubes.
It realizes high purity and precise morphology control of titanium carbide microtubes, reduces preparation cost and process complexity, and improves the chemical stability and electrical conductivity of the material, and is suitable for lithium-ion battery negative electrode materials.
Smart Images

Figure CN119706843A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic non-metallic material preparation, and specifically relates to a titanium carbide micron tube and a preparation method and application thereof. Background Art
[0002] Titanium carbide (TiC) is an important non-oxide ceramic material with unique physical and chemical properties, extremely high hardness, high melting point, low density, and good electrical and thermal conductivity. Based on the above characteristics, titanium carbide nanotubes have shown excellent properties in the fields of catalysts and electrode materials. However, problems such as the preparation cost, environmental impact, and stability of titanium carbide nanotubes have also emerged, and titanium carbide microtubes will be able to alleviate these problems to a certain extent.
[0003] The key to preparing TiC microtubes is how to control their micron-tube structure and achieve high-purity TiC materials. At present, the commonly used methods for preparing TiC microtubes include chemical vapor deposition (CVD), template method, solid-phase reaction method and other emerging nanofabrication technologies. The following are several main preparation methods: (1) Chemical vapor deposition (CVD) is a common technology for preparing TiC microtubes and is widely used in the preparation of high-purity, structure-controlled ceramic materials. This method uses a gaseous precursor to react chemically at high temperature to deposit TiC on a substrate. (2) The template method is to use a pre-designed template to deposit TiC on the surface or inside of the template, and then remove the template to obtain TiC microtubes. (3) The solid-phase reaction method uses a titanium source and a carbon source to react at high temperature to generate TiC. By selecting appropriate raw materials and reaction conditions, micron-tube-shaped TiC materials can be obtained. (4) The sol-gel method is a method for preparing ceramic materials through a solution chemical route. This method forms a titanium-based sol, which is then gelated and carbonized at high temperature to form TiC microtubes. (5) Carbothermal reduction is a method for preparing TiC by reducing titanium compounds with a carbon source. It is often used to prepare nano- or micron-sized TiC materials.
[0004] However, these traditional preparation methods all have shortcomings. For example, the solid-phase reaction method has a high reaction temperature and a long reaction time. The purity and morphology of the generated TiC microtubes cannot be precisely controlled, which to a certain extent limits the application scope of TiC microtubes. Several other preparation methods have the problems of high preparation cost and complex process. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a titanium carbide microtube and a preparation method and application thereof. The titanium carbide in the titanium carbide microtube prepared by the present invention has good chemical stability and conductivity, becoming a potential negative electrode material for lithium-ion batteries. Moreover, the microtube structure can provide a larger specific surface area and electron transmission path, which is conducive to the rapid embedding and de-embedding of lithium ions, thereby improving the capacity and cycle life of the battery.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing titanium carbide microtubes comprises the following steps:
[0008] In anhydrous ethanol solvent, SiC f As a template, mixed with Ti powder, heated and stirred, evaporated and ground to obtain a mixed powder.
[0009] The mixed powder is added to a mixed salt of NaCl and KCl, and a molten salt reaction is carried out under a protective atmosphere, Ti reacts in situ with SiC on the surface of the silicon carbide fiber, and SiC fiber containing a Ti3SiC2 coating is obtained through interface decomposition and diffusion mechanisms.
[0010] Under vacuum conditions, the SiC fiber containing the Ti3SiC2 coating is heat treated, Ti3SiC2 is decomposed into TiC and volatile Si, and a dense TiC layer is formed on the outer layer of the SiC fiber. As the reaction proceeds, the SiC fiber is completely decomposed to generate carbon and volatile Si, and the original template morphology of the SiC fiber is retained by TiC. The remaining Ti in the system further reacts with carbon through diffusion, and finally titanium carbide microtubes are obtained.
[0011] Since Ti reacts in situ with SiC on the surface of silicon carbide fiber to obtain a Ti3SiC2 coating of a certain thickness, the reaction process is as follows:
[0012] Ti+SiC→TiC+Si
[0013] Ti+2TiC+Si→Ti3SiC2
[0014] It is generated on the surface of SiC fiber to form a dense Ti3SiC2 phase. The reaction between Ti and the surface of SiC fiber is mainly carried out through interface decomposition and diffusion mechanism, and finally a stable Ti3SiC2 phase is formed.
[0015] Ti3SiC2 is a MAX phase material with a layered structure composed of Ti, Si and C. Under high temperature conditions, Ti3SiC2 will decompose to produce TiC, Si and other by-products: Ti3SiC2→3TiC+Si.
[0016] Under vacuum conditions, Si atoms generated at high temperatures are volatile, leaving behind residues with TiC as the main component. While decomposing and volatilizing, the residual TiC can form a tubular structure through surface diffusion and reorganization under high temperature. SiC fiber, as a substrate material, provides a template for the nucleation and growth of TiC after the decomposition of Ti3SiC2. Titanium carbide has excellent chemical stability, and at high temperatures, the material tends to reduce free energy. Therefore, during the decomposition process, TiC will preferentially grow along the fiber surface and form a micron-sized tubular structure guided by high temperature.
[0017] Under vacuum and high temperature conditions (1800°C), after part of the product Si volatilizes, it will be accompanied by local gas phase reaction and material migration. The material loss and internal stress relaxation caused by volatilization further promote the formation of a hollow structure of microtubes by TiC. In addition, in this system, the silicon of SiC fiber has a high vapor pressure and will volatilize rapidly under vacuum and high temperature conditions. The volatilized silicon causes SiC to lose the main element that supports its structural integrity. The carbon formed after decomposition generally remains temporarily in solid form, and then further diffuses, aggregates or reacts chemically with surrounding substances (such as forming TiC). As a result, the fiber gradually decomposes completely and is eventually replaced by a TiC tubular structure. The vacuum environment greatly reduces the partial pressure around the volatile substances, which further increases the volatilization rate of Si and the migration rate of carbon, thereby accelerating the decomposition of SiC.
[0018] Formation Mechanism of TiC Microtubes
[0019] Initial stage: reaction layer formation
[0020] The Ti3SiC2 coating decomposes at high temperature to generate TiC, forming a thin layer covering the surface of the SiC fiber. The Si produced by the decomposition gradually volatilizes, and the residual Ti further reacts with SiC to generate more TiC.
[0021] Intermediate stage: morphological transformation
[0022] As the reaction proceeds, the SiC fiber is gradually consumed, and carbon diffuses and reacts with Ti to form a dense TiC layer on the outer layer of the fiber. After the SiC fiber is decomposed, the growth rate of the carbon and Ti reaction is different on the fiber surface and in the pore area, gradually forming a hollow structure.
[0023] Final stage: complete fiber conversion
[0024] SiC fiber is completely decomposed under high temperature and vacuum, Si is completely volatilized, the original template morphology of the fiber is retained by TiC, and the remaining Ti further reacts with carbon through diffusion to form pure TiC microtubes.
[0025] The preparation of TiC microtubes by the raw materials and reaction conditions of the present invention depends on the following key mechanisms:
[0026] 1. SiC fiber provides a template, and the carbon produced by its decomposition provides source material for TiC formation.
[0027] 2. The Ti3SiC2 coating decomposes to generate initial TiC and promotes the transformation of the fiber into a TiC structure.
[0028] 3. High temperature and vacuum work together to drive Si volatilization, ensuring the formation of pure TiC structure and retaining the tubular morphology of the fiber.
[0029] By reasonably controlling the raw material ratio, coating thickness and reaction conditions, the morphology and properties of TiC microtubes can be precisely controlled.
[0030] In a preferred embodiment of the present invention, Ti powder and SiC f The molar ratio is 1:1~4.
[0031] In a preferred embodiment of the present invention, the molar ratio of NaCl to KCl is 1:1-4.
[0032] In a preferred embodiment of the present invention, the molar ratio of Ti powder to KCl is 1:10-15.
[0033] In a preferred embodiment of the present invention, the heat treatment temperature is 1800° C. to 1850° C., the heat treatment time is 40 min to 80 min, and the heat treatment heating rate is 5° C. / min to 10° C. / min.
[0034] In a preferred embodiment of the present invention, the molten salt reaction conditions are: firstly heat the temperature to 1050°C to 1150°C at a rate of 2°C / min to 5°C / min, keep warm for 20min to 40min, and then cool the temperature to 400°C to 600°C at a rate of 3°C / min to 6°C / min for reaction.
[0035] Another object of the present invention is to provide a titanium carbide microtube prepared by any of the preparation methods described above, wherein the mass fraction of titanium in the titanium carbide microtube is 55% to 65%, and the mass fraction of carbon is 35% to 45%, which is 100% in total.
[0036] The titanium carbide microtubes have good chemical stability and conductivity, making them potential negative electrode materials for lithium-ion batteries; the microtube structure can provide a larger specific surface area and electron transmission path, which is conducive to the rapid embedding and de-embedding of lithium ions, thereby improving the capacity and cycle life of the battery.
[0037] In a preferred embodiment of the present invention, the titanium carbide microtube is a tubular structure with a diameter of micrometer level.
[0038] The third object of the present invention is to provide an application of the titanium carbide microtubes described in any one of the above items in negative electrode materials for lithium-ion batteries.
[0039] The role and characteristics of raw material selection in the present invention:
[0040] SiC fiber as a template material has the following characteristics:
[0041] High temperature stability: SiC fiber will not decompose rapidly at 1800℃~1850℃, providing a physical support structure for the reaction.
[0042] Carbon source supply: SiC fiber decomposes at high temperature and releases carbon, which provides the necessary carbon source for the formation of TiC.
[0043] Ti3SiC2 coating material characteristics: Ti3SiC2 is a MAX phase material with a unique layered structure, which generates TiC and Si during thermal decomposition.
[0044] Mechanism of action: Ti3SiC2 decomposes into TiC and volatile Si at high temperature, which is conducive to the formation of TiC microtubes.
[0045] High purity titanium
[0046] Reaction driving force: Ti reacts chemically with SiC fibers and the carbon of the decomposition product to form TiC.
[0047] Morphology control: Ti has a strong diffusion ability and can be evenly distributed and participate in the reaction, promoting the growth of tubular TiC structure.
[0048] NaCl and KCl
[0049] The mixture of NaCl and KCl can form a low melting point eutectic salt, and the eutectic point of the NaCl-KCl system is about 657℃.
[0050] Molten salts can be used as solvents for high-temperature chemical reactions, promoting the dissolution of reactants and the migration of ions.
[0051] NaCl and KCl molten salts have strong fluidity at high temperatures and can evenly coat SiC fibers and titanium particles, ensuring that the reactants are fully in contact and forming a uniform coating structure.
[0052] NaCl and KCl molten salts provide low-resistance channels for the diffusion of Ti, Si and C, accelerating the migration of elements at the reaction interface.
[0053] Molten salt reduces the activation energy of the interface reaction between Ti and SiC and can lower the reaction temperature of the two.
[0054] In a high-temperature environment, the molten salt acts to isolate the air, preventing the reactants (especially titanium) from oxidation and ensuring the effective progress of the reaction.
[0055] Key effects of reaction conditions
[0056] Effects of high temperature (1800℃~1850℃):
[0057] SiC decomposition: SiC fiber decomposes at 1800℃~1850℃ to generate free Si (volatile) and carbon (solid or diffused state)
[0058] Ti3SiC2 decomposition: The coated Ti3SiC2 decomposes into TiC and volatile Si at high temperature:
[0059] Titanium diffusion and reaction: Titanium diffuses into the interface at high temperatures and reacts with the decomposed carbon to generate more TiC:
[0060] The role of vacuum environment:
[0061] Promote the removal of volatile products: Vacuum accelerates the volatilization of Si, making the reaction of carbon and titanium more thorough and reducing the formation of side phases.
[0062] Lower the decomposition temperature: Under vacuum environment, the decomposition temperature of SiC and Ti3SiC2 is lowered, and the reaction rate is enhanced.
[0063] The role of fiber structure:
[0064] The aspect ratio and hollow morphology of SiC fibers provide a template for the tubular growth of TiC at high temperatures. As SiC gradually decomposes, the original fiber structure is replaced by TiC.
[0065] Compared with the prior art, the TiC microtube material of the present invention focuses more on improving the performance of the TiC microtube material, and the reaction time is shorter, and the purity and morphology of the generated TiC microtubes can be more accurately controlled; and the present invention does not require subsequent template removal, the steps are relatively simple, the damage to the structure during the preparation process is smaller, and the preparation cost is reduced.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] 1. The preparation method of titanium carbide microtubes provided by the present invention comprises the following steps: fas a template, mixed with Ti powder, heated and stirred, evaporated and ground to obtain a mixed powder; the mixed powder is added to a mixed salt of NaCl and KCl, and a molten salt reaction is carried out under a protective atmosphere, Ti reacts with SiC on the surface of the silicon carbide fiber in situ, and SiC fiber containing Ti3SiC2 coating is obtained through interface decomposition and diffusion mechanism; the SiC fiber containing Ti3SiC2 coating is heat treated under vacuum conditions, and in the initial stage of the reaction: the Ti3SiC2 coating decomposes at high temperature to generate TiC, forming a thin layer covering the surface of the SiC fiber, the Si generated by the decomposition gradually volatilizes, and the residual Ti further reacts with SiC to generate more TiC; in the intermediate stage: as the reaction proceeds, the SiC fiber is gradually consumed, and carbon diffuses and reacts with Ti to generate a dense TiC layer on the outer layer of the fiber. After the SiC fiber is decomposed, the growth rate of the carbon and Ti reaction is different on the fiber surface and the hole area, gradually forming a hollow structure; the final stage: the SiC fiber is completely decomposed under high temperature and vacuum, Si is completely volatilized, the original template morphology of the fiber is retained by TiC, and the remaining Ti further reacts with carbon through diffusion to form pure TiC microtubes. The TiC microtube material of the present invention pays more attention to improving the performance of the TiC microtube material, and the reaction time is short, and the purity and morphology of the generated TiC microtube can be more accurately controlled; and the present invention does not need to remove the template later, the steps are relatively simple, the damage to the structure during the preparation process is less, and the preparation cost is reduced.
[0068] 2. The titanium carbide microtube of the present invention is obtained by high-temperature treatment of SiC fiber containing Ti3SiC2 coating. TiC has a unique electronic structure and physical properties, and has high electron mobility. The material of the TiC microtube has good electrochemical properties. The material contains highly conductive metal TiC, so the material has good conductivity.
[0069] 3. The titanium carbide microtube structure prepared by the present invention can provide a larger specific surface area and electron transmission pathway, which can effectively improve the capacity of the lithium battery. The microtube structure is conducive to the rapid embedding and de-embedding of lithium ions, and has the characteristic of improving the cycle life of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 In the figure, (a) to (c) are morphological images of titanium carbide microtubes prepared in Example 1 of the present invention at different magnifications.
[0071] Figure 2 This is the EDS energy spectrum of the titanium carbide microtube prepared in Example 1 of the present invention.
[0072] Figure 3 This is the XRD pattern of the titanium carbide microtubes prepared in Example 1 of the present invention.
[0073] Figure 4This is the resistivity test result of the titanium carbide microtube prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0074] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0075] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0076] Example 1
[0077] A method for preparing titanium carbide microtubes comprises the following steps:
[0078] (1) SiC f The SiC and Ti powders were added to anhydrous ethanol and heated and stirred with a heating magnetic stirrer until all the ethanol was evaporated and discharged, and then ground and mixed again in a mortar. f The molar ratio of Ti powder to Ti powder is 2:1 to obtain a mixed powder.
[0079] (2) NaCl and KCl powders are mixed at a molar ratio of 10:10 to obtain a mixed salt, and the mixed powder and the mixed salt are mixed to obtain a final mixture for later use.
[0080] (3) The alumina crucible containing the above mixture is placed in a tubular furnace with argon gas flowing to react and prepare SiC fibers containing Ti3SiC2 coating. The specific process of reaction preparation is: first increase the temperature to 1100°C at a rate of 4°C / min, keep warm for 30 minutes, and then cool down to 500°C at a rate of 4°C / min for reaction.
[0081] (4) After the sample is taken out, the mixed salt in the system is completely removed, and the deionized water is removed by drying to obtain the SiC fiber material containing the Ti3SiC2 coating, which is recorded as SiC f -T.
[0082] (5) Under vacuum conditions, SiC f -T is placed in a graphite carbon tube furnace for high temperature heat treatment at 1800℃ for 60min, with a heating rate of 8℃ / min, and finally a TiC tube with a diameter of micrometer level is obtained.
[0083] Example 2
[0084] A method for preparing titanium carbide microtubes comprises the following steps:
[0085] (1) SiC f The SiC and Ti powders were added to anhydrous ethanol and heated and stirred with a heating magnetic stirrer until all the ethanol was evaporated and discharged, and then ground and mixed again in a mortar. f The molar ratio of Ti powder to Ti powder is 1:1 to obtain a mixed powder.
[0086] (2) NaCl and KCl powders are mixed at a molar ratio of 10:15 to obtain a mixed salt, and the mixed powder and the mixed salt are mixed to obtain a final mixture for later use.
[0087] (3) The alumina crucible containing the above mixture is placed in a tubular furnace with argon flowing to carry out reaction preparation of SiC fibers containing Ti3SiC2 coating. The specific process of reaction preparation is: first increase the temperature to 1050°C at a rate of 2°C / min, keep warm for 20 minutes, and then cool down to 400°C at a rate of 3°C / min for reaction.
[0088] (4) After the sample is taken out, the mixed salt in the system is completely removed, and the deionized water is removed by drying to obtain the SiC fiber material containing the Ti3SiC2 coating, which is recorded as SiC f -T.
[0089] (5) Under vacuum conditions, SiC f -T is placed in a graphite carbon tube furnace for high temperature heat treatment at 1820°C for 80 minutes with a heating rate of 5°C / min, and finally a TiC tube with a diameter of micrometer level is obtained.
[0090] Example 3
[0091] A method for preparing titanium carbide microtubes comprises the following steps:
[0092] (1) SiC f The SiC and Ti powders were added to anhydrous ethanol and heated and stirred with a heating magnetic stirrer until all the ethanol was evaporated and discharged, and then ground and mixed again in a mortar. f The molar ratio of Ti powder to Ti powder is 4:1 to obtain a mixed powder.
[0093] (2) NaCl and KCl powders are mixed at a molar ratio of 10:12 to obtain a mixed salt, and the mixed powder and the mixed salt are mixed to obtain a final mixture for later use.
[0094] (3) The alumina crucible containing the above mixture is placed in a tubular furnace with argon gas flowing to carry out reaction preparation of SiC fibers containing Ti3SiC2 coating. The specific process of reaction preparation is: first increase the temperature to 1150°C at a rate of 5°C / min, keep warm for 40 minutes, and then cool down to 600°C at a rate of 6°C / min for reaction.
[0095] (4) After the sample is taken out, the mixed salt in the system is completely removed, and the deionized water is removed by drying to obtain the SiC fiber material containing the Ti3SiC2 coating, which is recorded as SiC f -T.
[0096] (5) Under vacuum conditions, SiC f -T is placed in a graphite carbon tube furnace for high temperature heat treatment at 1850°C for 40 minutes with a heating rate of 10°C / min, and finally a TiC tube with a diameter of micrometer level is obtained.
[0097] Results Analysis
[0098] Figure 1 In the figure, (a) to (c) are morphological images of titanium carbide microtubes prepared in Example 1 of the present invention at different magnifications. It can be seen from the figure that the diameter of the tubular titanium carbide is about 10.80 μm and the inner wall thickness is about 1.70 μm. The results show that titanium carbide microtubes with no obvious pores in the tube wall and uniform and dense microstructure can be prepared under the experimental conditions. If the fiber raw materials are cut to different sizes, microtubes with different aspect ratios can be prepared.
[0099] Figure 2 This is the EDS spectrum of the titanium carbide microtube prepared in Example 1 of the present invention. Figure 2 The EDS spectrum analysis of the corresponding area is shown in Table 1. The mass fraction of Ti element is 62.57%, and the mass fraction of C element is 35.63%. Cu and Zn elements are the main components of the sample carrier in the instrument test, and their contents can be ignored. Figure 3 Phase analysis of the titanium carbide microtubes prepared in Example 1 of the present invention shows that the main phase composition of the titanium carbide microtubes is TiC without other impurities, which proves that the method can prepare high-purity titanium carbide microtubes with uniform microstructure.
[0100] Table 1 Spectrum Figure 2 EDS spectrum analysis
[0101]
[0102] The conductivity data of the TiC microtubes prepared by the present invention are as follows: Figure 4As shown in Table 2, it can be seen that when the initial pressure is only 1.99MPa, the conductivity of the titanium carbide microtube reaches 103.62S / cm, which has high conductivity. As the pressure increases to 30.02MPa, the conductivity of the titanium carbide microtube reaches 577.18S / cm. The conductivity is usually positively correlated with the density and porosity of the material. Excessive porosity will cause the conductive channel of the material to be interrupted and the conductivity to decrease. Therefore, when the compaction density of the material increases, the porosity decreases and the conductivity increases. As the pressure increases, the contact between the powder particles becomes closer, thereby improving the conduction path of the electrons and increasing the conductivity. The conductivity of the titanium carbide microtube material shows a gradual upward trend with the increase in pressure until it reaches a certain saturation point, that is, further increasing the pressure has little effect on the conductivity.
[0103] Specifically, at the low pressure stage: when the pressure is low, the contact between the powder particles is incomplete, the compaction density is low, the porosity is high, and the conductivity is low. As the pressure increases, the particles are gradually compacted, the porosity decreases, and the conductivity begins to increase.
[0104] Medium pressure stage: In this stage, as the compaction density increases, the contact between particles is good and the conductivity increases rapidly. At this time, the conduction path of electrons is gradually optimized, and the conductivity shows a significant upward trend.
[0105] High pressure stage: When the pressure reaches a certain value, the further compaction effect of the powder particles weakens, and the increase in conductivity tends to saturation. At this time, the change in conductivity is relatively gentle, and the curve tends to be stable.
[0106] The TiC microtube prepared by the present invention has a high compaction density and an excellent crystal structure, and the electrical conductivity of the material tends to be stable as the pressure increases. This indicates that it can maintain excellent electrical conductivity under a certain pressure and compaction density, can effectively conduct current, and the performance is relatively stable to environmental conditions (such as temperature, pressure, etc.), and can be used as an electrode material for equipment such as batteries, capacitors or electrolytic cells, meeting the needs of modern high-performance, high-temperature resistant and highly conductive materials, and improving their working efficiency and stability.
[0107] Table 2 Conductivity data of TiC microtubes
[0108]
[0109] In summary, the method for preparing titanium carbide microtubes provided by the present invention is to prepare SiC fas a template, mixed with Ti powder, heated and stirred, evaporated and ground to obtain a mixed powder; the mixed powder is added to a mixed salt of NaCl and KCl, and a molten salt reaction is carried out under a protective atmosphere, Ti reacts with SiC on the surface of the silicon carbide fiber in situ, and SiC fiber containing Ti3SiC2 coating is obtained through interface decomposition and diffusion mechanism; the SiC fiber containing Ti3SiC2 coating is heat treated under vacuum conditions, in the initial stage: the Ti3SiC2 coating is decomposed at high temperature to generate TiC, forming a thin layer covering the surface of the SiC fiber, the Si generated by the decomposition gradually volatilizes, and the residual Ti further reacts with SiC to generate more TiC; in the intermediate stage: as the reaction proceeds, the SiC fiber is gradually consumed, and carbon diffuses and reacts with Ti to generate a dense TiC layer on the outer layer of the fiber. After the SiC fiber is decomposed, the growth rate of the carbon and Ti reaction is different on the fiber surface and the hole area, gradually forming a hollow structure; the final stage: the SiC fiber is completely decomposed under high temperature and vacuum, Si is completely volatilized, the original template morphology of the fiber is retained by TiC, and the remaining Ti further reacts with carbon through diffusion to form pure TiC microtubes. The TiC microtube material of the present invention pays more attention to improving the performance of the TiC microtube material, and the reaction time is short, and the purity and morphology of the generated TiC microtube can be more accurately controlled; and the present invention does not need to remove the template later, the steps are relatively simple, the damage to the structure during the preparation process is less, and the preparation cost is reduced.
[0110] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0111] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing titanium carbide microtubes, characterized in that: The following steps are involved: In anhydrous ethanol solvent, SiC f As a template, it is mixed with Ti powder, heated and stirred, evaporated and ground to obtain a mixed powder; The mixed powder is added to a mixed salt of NaCl and KCl, and a molten salt reaction is carried out under a protective atmosphere, Ti reacts in situ with SiC on the surface of the silicon carbide fiber, and SiC fiber containing a Ti3SiC2 coating is obtained through an interface decomposition and diffusion mechanism; Under vacuum conditions, the SiC fiber containing the Ti3SiC2 coating is heat treated, Ti3SiC2 is decomposed into TiC and volatile Si, and a dense TiC layer is formed on the surface of the SiC fiber. As the reaction proceeds, the SiC fiber is completely decomposed to generate carbon and volatile Si, the original template morphology of the SiC fiber is retained by TiC, and the remaining Ti in the system further reacts with carbon through diffusion, and finally titanium carbide microtubes are obtained.
2. The method for preparing titanium carbide microtubes according to claim 1, characterized in that: Ti powder and SiC f The molar ratio is 1:1~4.
3. The method for preparing titanium carbide microtubes according to claim 1, characterized in that: The molar ratio of NaCl to KCl is 1:1-4.
4. The method for preparing titanium carbide microtubes according to claim 1, characterized in that: The molar ratio of Ti powder to KCl is 1:10-15.
5. The method for preparing titanium carbide microtubes according to claim 1, characterized in that: The heat treatment temperature is 1800°C to 1850°C, the heat treatment time is 40min to 80min, and the heat treatment heating rate is 5°C / min to 10°C / min.
6. The method for preparing titanium carbide microtubes according to claim 1, characterized in that: The molten salt reaction conditions are: firstly heat up to 1050°C to 1150°C at a rate of 2°C / min to 5°C / min, keep warm for 20min to 40min, and then cool down to 400°C to 600°C at a rate of 3°C / min to 6°C / min for reaction.
7. A titanium carbide microtube obtained by the preparation method according to any one of claims 1 to 6, characterized in that: In the titanium carbide microtube, the mass fraction of titanium is 55% to 65%, and the mass fraction of carbon is 35% to 45%, which is 100% in total.
8. The titanium carbide microtube according to claim 7, characterized in that: The titanium carbide microtube is a tubular structure with a diameter of micrometer level.
9. Use of the titanium carbide microtube according to claim 7 in negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
SiC / TiC layered composite material and preparation method thereof
CN112919912A
Unbonded integrated titanium carbide material and preparation method thereof
CN113401906A
Method for in-situ synthesis of Ti-Si-C composite interface phase on surface of silicon carbide fiber
CN118164767A
Microtube titanium carbonate base fibre and its preparation process
CN1394829A
Method for producing titanium silicon carbide
JP2012087009A